Mapeamento de competências com base no planejamento estratégico das organizações: proposta de metodologia - Mussi, Ana Paula Toledo Machado (2011)
In a globalized and highly competitive environment, the definition of strategies becomes an indispensable element to the success of organizations. Strategic management presents more necessary the greater the complexity of decisions that need to be taken. The management and strategic planning are intimately related to the competency management, given that the achievement of the tasks described in these plans is directly related to human resources capacity. Thus, for a company to succeed, it is necessary that human resources and strategic planning to walk in the same direction. The survey, in its conceptual part, presents concepts of competences and their mapping and strategic planning. Field work begins with a survey of competences and strategic knowledge to organizations through reading their maps / strategic planning and aims to present an alternative that allows the construction of a model of mapping of individual competences to meet the strategic objectives of the organizations. This research is characterized as action research and the field served were the entities that make up the Federation of Industries of Paraná - FIEP, namely SESI, SENAI, IEL and FIEP.